Phytoplankton composition of Muara Tebas and its related environmental condition - Hiew, Hua Kui (Universiti Malaysia Sarawak (UNIMAS), 2014)
Harmful Algae Bloom (HABs) is not negligible as it is threat to human health, ecosystem and environment. Occurrences of phytoplankton are highly dependent on the environmental condition. This study is initiated to understand the influence of physicochemical to the production and growth of phytoplankton species in tropical countries. Study was carried out at Muara Tebas estuary as anthropogenic activities and development site is commonly seen. Qualitative and quantitative samples were collected from October 2013 to February 2014. Chemical parameters such as nutrient concentration and chlorophyll a showed to have direct impact on cell density trend. Cell abundance had correlation with the presence of macronutrient especially orthophosphate and silicate. Conversely, physical parameters showed weak relation to cell density with exception to temperature.Cell density also influenced by northeast monsoon (NEM) as the precipitation and upwelling in west coast of Sarawak. A total of 18 taxa of phytoplankton were found and identified to genus level, with 15 diatom (8 penates and 7 centric), 2 dinoflagellates and 1 cyanobacteria.